Non-Conventional Information Services: An Experience of College Librarians and Users (International Journal of Scientific Research in Science and Technology, 2024)
This paper briefly describes the experience of college librarians and users of the Gadchiroli district affiliated with Gondwana University, Gadchiroli, regarding non-conventional information services provided by college libraries. The virtual mini survey method was adopted. In the experience of librarians, research has shown that various factors affect information services. This includes 93% technical items, 90% financial assistance, 87% administrative aspects, and 91% infrastructural facilities. According to various users, libraries lacked 82% of the resources needed to provide non-conventional information services to users. Librarians have reported their experiences on 80% of the various aspects of non-conventional services, and they noted that readers felt that 50% of the services should be available via mobile phones. Based on librarians’ and users’ experiences with non-conventional information services in college libraries, it was concluded that users prefer mobile-based information services. Libraries should recognize emerging needs and embrace new technologies to serve the interests of their users in evolving circumstances. The experiences of librarians and users in information services are quite useful for future improvements.